An investigation into internationalization motives, export barriers and the export marketing strategies that effect exporting performance of Thai textile SME Company - Eowpittayakul, Pongsakorn (2007)
This dissertation looks at the experiences of exporting textile SME Company in Thailand. The aims of this project are to get an insight view into how Thai firm's export motivation. Moreover, the study is to find the export barriers that affect the firm export performance in different ways. This study further investigated into firm export marketing strategies that affect the firm export performance in a particular area.